The effect of green human resources management practices on corporate sustainability from the perspective of employees - Sima Nart; Ahmet Bilgili; Emine Demet Orgut (Economics: The Open-Access, Open-Assessment Journal, 2024)
This study examines the impact of Green Human Resources Management (GHRM) in the textile and fashion industry on corporate sustainability (CS). In addition, the indirect effects of organizations' environmental performance (EP) and employee commitment to CS are also examined. The research was carried out with the participation of the employees (n = 129) of Turkish organizations operating in the fashion and textile sector that adopt a sustainable business management approach. Structural equation modeling via smart PLS was used for data analysis. The findings showed that GHRM positively affects CS, and EP mediates this relationship. However, employee commitment did not have a mediating effect in this relationship. These results provide CS experts and managers with evidence-based insights into designing GHRM practices and sustainability strategies.
Keywords: M1; M10; M14; 330; corporate sustainability; sustainability; green human resources management; environmental performance; employee commitment